Phenotypic and Genotypic Investigation of Carbapenem-Resistant Acinetobacter baumannii in Maharaj Nakhon Si Thammarat Hospital, Thailand - Sirijan Santajit; Phuangthip Bhoopong; Thida Kong-Ngoen; Witawat Tunyong; Dararat Horpet; Wanfudhla Paehoh-ele; Tasneem Zahedeng; Pornpan Pumirat; Nitat Sookrung; Woranich Hinthong; Nitaya Indrawattana (Antibiotics, 2023)
(1) Background: Acinetobacter baumannii is well known as a causative agent of severe hospital-acquired infections, especially in intensive care units. The present study characterised the genetic traits of biofilm-forming carbapenem-resistant A. baumannii (CRAB) clinical isolates. Additionally, this study determined the prevalence of biofilm-producing A. baumannii isolates from a tertiary care hospital and investigated the association of biofilms with the distribution of biofilm-related and antibiotic resistance-associated genotypes. (2) Methods: The 995 non-duplicate A. baumannii isolates were identified, and their susceptibilities to different antibiotics were determined using the disk diffusion method. Using the modified microtiter plate assay, the CRAB isolates were investigated for their biofilm formation ability. Hemolysin and protease activities were determined. CRABs were subjected to polymerase chain reaction (PCR) assays targeting blaVIM, blaNDM, blaIMP, blaOXA-23-like, blaOXA-24-like, blaOXA-51-like, csuE and pgaB genes. Individual CRAB isolates were identified for their DNA fingerprint by repetitive element sequence-based (REP)-PCR. (3) Results: Among all A. baumannii isolates, 172 CRABs were identified. The major antibiotic resistance gene among the CRAB isolates was blaOXA-51-like (100%). Ninety-nine isolates (57.56%) were biofilm producers. The most prevalent biofilm gene was pgaB (79.65%), followed by csuE (76.74%). Evidence of virulence phenotypes revealed that all CRAB exhibited proteolytic activity; however, only four isolates (2.33%) were positive for the hemolytic-producing phenotype. REP-PCR showed that 172 CRAB isolates can be divided into 36-DNA fingerprint patterns. (4) Conclusions: The predominance of biofilm-producing CRAB isolates identified in this study is concerning. The characterisation of risk factors could aid in controlling the continual selection and spreading of the A. baumannii phenotype in hospitals, thereby improving patient care quality.